Soundings documentary film and the listening experience - Cox, Geoffrey; Corner, John (University of Huddersfield Press, 2018)
This book draws on the lived experience of sound's capacity to move and shake us in direct, subtle and profound ways through speech, location sound, and music in documentary film. The associative, connotative and sheer emotive power of sound has the capacity to move and shake us in a myriad of direct, subtle and often profound ways. The implications of this for its role as speech, location sound, and music in documentary film are far-reaching. The writers in this book draw on the lived experience of sound's resounding capacity as primary motivation for exploring these implications, united by the overarching theme of how listening is connected with acts of making sense both on its own terms and in conjunction with viewing. The resulting thirteen essays of Soundings: Documentary Film and the Listening Experience cover films made from WWII to the present day in locations across Europe and the Americas, and in styles ranging from political propaganda, industrial promotion and educative exposition, to more aesthetically-driven films taking their bearings from avant-garde art. The authors draw on their experience in scholarly research, practice-as-research, and in the aesthetic and technical practice of documentary filmmaking. This mix of perspectives aims to widen and deepen the outlook of the recent and growing academic interest in the topic of documentary film sound.